POTENSI SEKAM PADI DAN JERAMI SEBAGAI ALTERNATIF MATERIAL AKUSTIK - Rohim, Ahmad Minanur; Fianti, Fianti; Nurbaiti, Upik (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
Technology that is increasingly developing produces equipments in the form of information, communication, production, transportation and entertainment facilities. Most of the equipments produce noises. Noise can be reduced by using acoustic dampers. This study aims to determine the potential for sound absorption from rice husks and straw as natural acoustic materials. Materials used include rice husks, rice straw, and resin. 12 cylindrical samples were made. Samples that have been made are tested using a sound absorption measuring instrument that is the impedance tube to measure the value of the sample sound absorption coefficient. The test results show the value of the sound absorption coefficient (?) can be influenced by the thickness. At a frequency of 500 Hz the value of the sound absorption coefficient (?) for each sample is 0.034dB; 0.030dB; 0.030dB; 0.027dB; 0.026dB; 0.027dB; 0.025dB; 0.025dB; 0.025dB; 0.024dB; 0.024dB; 0.023dB; 0.023dB. The sample material is good in research on materials 1 and 2 which have a sound absorption of 0.034 dB and 0.030 dB.